PERANCANGAN DAN IMPLEMENTASI PERANGKAT LUNAK PROXY TUNNEL DENGAN ENKRIPSI KUNCI SIMETRISASIMETRIS UNTUK MANIPULASI PAKET DATA - Gat Gat (SISFOTENIKA, 2011)
Abstracts: The authors conducted a study on wiretapping in computer networks because of it is very disturbing security and comfort in the surf. Therefore the writer create a proxy tunnel software with symmetric and asymmetric encryption as a security agent that encrypts data communications conducted. Forms of research that the author did was experimental data collection techniques onegroup posttest-pretest, the authors study variable is the security of data packets transmitted between website and browser. Design method used is the Extreme Programming with 4 ways to apply the practical development of XP, namely coding, testing, listening and designing. The result is a software design software called "Crypto Tunnel Proxy", according to the function of encryption, tunneling and proxy. The software engineering author uses Visual Basic 6.0 and uses 2 types of encryption, namely symmetrical and asymmetrical. The authors also apply the hash function as a fingerprint or fingerptint of keys that are sent. This application can improve security in computer networks. By encrypting all data packets between the browser and the website are symmetrical and asymmetrical. Tests conducted with several commonly used browsers.Keywords: RC4 and RSA Encryptiom, Tunneling, Proxy